SCIENTIFIC ATTITUDE TO CONSCIOUSNESS AND ITS INFLUENCE ON THE FIELD OF EDUCATION - Yuldasheva, Dilorom (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article discusses the evolution of the scientific field since the end of the XIX century, when science became not only a system of knowledge, but also a key factor in the development of society. Changes in the social status of science influenced its internal organization, turning it into an important social institution. The article emphasizes the expanding influence of scientific consciousness on public opinion and the need to improve educational systems to popularize scientific knowledge. Next, the author discusses the arguments in favour of a scientific attitude of consciousness related to the representation of natural and social reality, as well as the role of science in the fight against superstition and the spread of humanism. The formation of a scientific attitude of consciousness requires a deep understanding of the history of culture, which allows individuals to critically evaluate information and conclusions and resist traditional attitudes of thinking.